PENGEMBANGAN APLIKASI KALENDER PENJADWALAN BERBASIS WEBSITE PADA DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN BADUNG - I Gusti Ngurah Made Dika Varuna; I Gusti Agung Gede Arya Kadyanan; I Made Widhi Wirawan (Jurnal Pengabdian Informatika, 2024)
In this digital era, technological developments are progressing very rapidly. Everyone is able to access technology that is applied in every area of ​​life. A calendar is a system for naming certain time periods. Naming this time period can be based on the activities that will be carried out. Employees of the Badung Regency Communication and Informatics Service have many activities and events that are difficult to organize, both from activities held in the field, department and outside the duties of the agency itself. There is a problem that occurs in agencies, namely that employees often do not remember the schedule that will be held in the future because there are many official events both internally within the agency and externally outside the agency, such as meetings within the agency or at other agencies in Badung Regency. The author tries to design the development of a scheduling calendar application with user roles to make it easier for employees in agencies to make it easier to manage their schedules. The creation of this system has been approved by the person in charge of the agency and can also be used as the result of field work practice and published in a journal.